2020
DOI: 10.1002/jctb.6447
|View full text |Cite
|
Sign up to set email alerts
|

A novel environment‐friendly synthetic technology of dibutyl itaconate

Abstract: BACKGROUND: In this work, a novel environment-friendly synthesis technology of dibutyl itaconate (DBI) with lipase as catalyst was developed. The effects of various parameters, like the sorts and amounts of lipase, reaction temperature, solvent, molar ratio of substrates, dehydrant, reactor and the reaction time have been studied and optimized. The reuse rate of lipase has been evaluated. RESULTS: The highest conversion rate of IA was 61.8% with 97.3% purity of DBI. The optimal reaction conditions were as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…This behavior could be due to the fact that the DBI produces some plasticization effect into polymer matrices [ 46 ]. The introduction of a plasticizer reduces tensile modulus and tensile strength, and at the same time the elongation increases with regard to the other compounds studied; all these phenomenon can be explained by several plasticization theories, such as the lubricity, gel and free volume theories [ 47 , 48 ]. With the introduction of PBSA- g -IA and PBSA- g -MA copolymers into the BioPBSA/HEMP, the tensile modulus and tensile strength results are 2505 MPa and 23.2 MPa, respectively, for the BioPBSA/HEMP/PBSA- g -IA composite, and 2748 MPa and 29.1 MPa for the BioPBSA/HEMP/PBSA- g -MA.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior could be due to the fact that the DBI produces some plasticization effect into polymer matrices [ 46 ]. The introduction of a plasticizer reduces tensile modulus and tensile strength, and at the same time the elongation increases with regard to the other compounds studied; all these phenomenon can be explained by several plasticization theories, such as the lubricity, gel and free volume theories [ 47 , 48 ]. With the introduction of PBSA- g -IA and PBSA- g -MA copolymers into the BioPBSA/HEMP, the tensile modulus and tensile strength results are 2505 MPa and 23.2 MPa, respectively, for the BioPBSA/HEMP/PBSA- g -IA composite, and 2748 MPa and 29.1 MPa for the BioPBSA/HEMP/PBSA- g -MA.…”
Section: Resultsmentioning
confidence: 99%
“…Bio-based dibutyl itaconate was obtained by our group in Beijing University of Chemical Technology . Other chemicals used, reagents, and solvents were analytically pure and purchased commercially.…”
Section: Methodsmentioning
confidence: 99%
“…The study investigated the working mechanism of the pyrotechnic binder and the combustion process thereof to provide new strategies for a controllable combustion rate and clean combustion products. 8 Other chemicals used, reagents, and solvents were analytically pure and purchased commercially. They include 5-AT from Mobe (Shanghai) Biotech Co., Ltd. and potassium nitrate, benzoyl peroxide, and phenolic resin (PF) from Beijing Tongguang Fine Chemicals Company.…”
Section: Introductionmentioning
confidence: 99%
“…An orbital shaker would be placed in the reaction pot, and external agitation is applied. Based on Table S1, it can be seen that the residence time required for reaction systems that employ external agitation/ orbital shakers require longer residence times in order to achieve high product yield, with an average time of 24 h, where the longest residence time is reported to be 72 h. 32,46,50,51 In comparing the two agitation systems, Yu et al found that the conversion rate of itaconic acid at 65 °C is higher in a magnetic stirring system at a yield of 61.8% at 72 h, and the conversion rate is at 47.5% at 120 h for an external agitation system. The authors explained that stirring by a magnetic stirrer is more intense and promotes contact between the substrate and the enzyme.…”
Section: Type Of Reactors Used and Choice Of Enzymes In Biocatalysismentioning
confidence: 99%
“…46 Yu et al reports that Novozym 435 can produce a high purity product due to the enzyme's high selectivity that will cleave specific bonds. 46 3.7. Reusability of the Enzyme.…”
Section: Overview Of Reaction Conditionsmentioning
confidence: 99%